FORMATION OF THE EUROPEAN PART OF THE CITY OF SAMARKAND IN THE XIX-XX CENTURIES, AS WELL AS THEIR APPLICATION IN THE TOURISM INDUSTRY (Academicia Globe: Inderscience Research, 2023)
This article deals with the formation of the European part of the city of Samarkand and the use of historical streets and objects in the tourism industry. As well as recommendations for conservation and reconstruction in this part of this city.